إستناد الممكنات إلى هللا تعالى إبتدا ًء عند األشاعرة: - Abdullah Mohammed Kareem (QALAAI ZANIST JOURNAL, 2019)
A research title based on all the possibilities to God, starting with the poet, a book explaining the positions model, I spoke briefly about the doctrine of Al shayra in this subject, and made it in the introduction and two topics, the first topic: With regard to this subject doctrinal issues through two demands: And the second requirement: with regard to the living and the time, and with them when the poet The second topic: I devoted it to this issue of verbal issues, through two demands: First demand: It showed the issue of obstetrics any effects of the acts, and respond to the Mu’tazilah, and the second requirement: I spoke about the good and ugliness, and the best of the slave with the response to the Mu’tazila, Then comes the conclusion, then the names of the sources, and the conclusion of the research in Arabic and English.